Naming Traditional Javanese Food Based on The Experience of The Sense of Motion - ., Sunarya; Kurniati Werdiningsih, Yuli; ., Alfiah (KnE Social Sciences, 2022)
Various Javanese foods have the same ingredients and taste, but they vary in name based on the region it is made in. The difference is caused by people’s sensual expressions based on the traditional food they have. The senses discussed in this paper are limited to the sense of motion. This paper uses a qualitative method to explain and describe various data points. The analysis techniques used were direct (agih) and indirect (padan). The direct technique is an analysis of language elements, in this case, related to the formation of words that are used as food names; while the indirect technique is an analytical technique that connects elements of language with elements outside of language, in this case, related to the iconic depiction of the human senses. The results showed that the name of the foods was motivated by the description of the sense of motion, such as cucur, sawut, cenil, ongol-ongol, gablok, jadah, and oblok-oblok. Keywords: traditional food; sense of motion; language elements